Invisible cervical cancers on MRI: Can the type of histology (SCC versus non-SCC) influence surgical planning? - Jeon, Jungeun; Park, Byung Kwan; Lee, Jeong-Won; Choi, Chel Hun; Lee, Yoo-Young; Kim, Tae-Joong; Kim, Byoungi-Gie (Frontiers in Oncology, 2022)
Background: Invisible cervical cancers on MRI can indicate less invasive surgery. Cervical cancers consist of squamous cell carcinoma (SCC) and non-SCC, and theeach with different long-term outcomes are different each other. It is still unclear if surgical planning should be changed according to the histologic type of cervical cancers when it is invisible not visible on MRI. Purpose: To determine if surgical planning for cervical cancer that is not visible on MRI is influenced by the histologic type of. cervical cancers which are invisible on MRI. Materials and Methods: Between January 2007 and December 2016, (155) women had a Federation of Gynecology and Obstetrics (FIGO) stage 1B1 cervical cancer which that was invisible not visible on pre-operative MRI. They underwent radical hysterectomy hysterectomies and pelvic lymph node dissections. Among them, (88) and (67) were histologically diagnosed as with SCC and non-SCC, respectively. These groups were compared regarding Tthe size of the residual tumor, depth of stromal invasion, parametrial invasion, vaginal invasion, lympho-vascular invasion, and lymph node metastasis were compared between these patients using thewith t-test, Mann-Whitney U test, Chi-squared test, or Fisher’s Exact test. RecurrenceThe recurrence-free and overall 10-year survival rates were compared between these groups with by Kaplan-Meyer analysis. Results: The mean sizes of residual tumor were 8.4±10.4 mm in the SCC group and 12.5 ± 11.9 mm in the non-SCC group (p=0.024). The mean depth of stromal invasion in the SCC group was 12.4±21.2% (0 – 100%), whereas that in the non-SCC group was 22.4±24.4 (0–93%) (p=0.016). However, there was no difference regarding in parametrial or vaginal invasion, lympho-vascular invasion, and or lymph node metastasis (p = 0.504 – 1.000). The recurrence-free and overall 10-year survival rates were (98.9)% (87/88) and (95.5)% (64/67) (p = 0.246), and (96.6)% (85/88) and (95.5)% (64/67) (p=0.872), respectively. Conclusions: NonThe non-SCC group tends to have a larger size of residual tumors or and a greater depth of stromal invasion than the SCC grouop, even though both are inneither is visible on MRI. Therefore, a meticulous care is necessary to for apply performing parametrectomy parametrectomy in patients with non-SCC cervical cancer.